Association of endogenous testosterone with subclinical atherosclerosis in men: the multi‐ethnic study of atherosclerosis. (2nd February 2016) - Khazai, Bahram; Golden, Sherita Hill; Colangelo, Laura A.; Swerdloff, Ronald; Wang, Christina; Honoris, Lily; Gapstur, Susan M.; Ouyang, Pamela; Cushman, Mary; Li, Dong; Kopp, Peter; Vaidya, Dhananjay; et al.
Summary: Objectives: Whether endogenous sex hormones play a role in cardiovascular disease (CVD) risk in men is unclear. Few studies have examined associations of sex hormones with atherosclerosis measured by coronary artery calcium score (CACS) and carotid intima‐media thickness (cIMT). We evaluated the association of testosterone (T) and other sex hormones with CACS and cIMT. Methods: Using the large multi‐ethnic cohort of 3164 men without known CVD in the Multi‐Ethnic Study of Atherosclerosis (MESA), cross‐sectional associations of tertiles of endogenous sex hormones with CACS and cIMT were analysed. Results: In regard to CAC, there was a significant negative trend (P‐trend = 0·02) for CACS>0 over tertiles of free T (FT) with RRs (95% CI) for the lowest to highest tertiles. There was also a marginally significant positive trend (P‐trend = 0·06) for CACS>0 over tertiles of sex hormone‐binding globulin (SHBG) with RRs for the lowest to highest tertiles. There were no significant associations with CACS >0 for tertiles of TT (Total T), bioavailable T (BT), oestradiol (E2) and dehydroepiandrosterone (DHEA). There was significantly higher log CACS after adjustment for CVD risk factors for lower TT levels, compared to higher levels, using 9·54 and 10·4 nmol/l as cut‐off points. In regard to cIMT, there was a significant positive trend ( P = 0·003) in mean cIMT over the tertiles of BT, but not for TT, FT, E2, DHEA and SHBG. There was significantly lower cIMT after adjustment for CVD risk factors for lower TT levels compared to higher levels. Conclusion: In a population of male subjects with no known CVD, lower FT is associated with higher RR of CACS>0 and lower TT is associated with higher log CACS. Lower BT and TT are associated with lower cIMT. While these findings support the positive correlation between low T and coronary atherosclerosis, the opposite findings on cIMT warrant further evaluation.